A Review: Integration of Renewable Energies in the Sustainability of the Electric Distribution Grid - Castro, Adalberto Ospino; Troncoso-Mendoza, Sonni; Gallardo, Rafael PeÃ±a; Zamora-Musa, Ronald (International Journal of Energy Economics and Policy, 2021)
This Article submits a review of the integration of renewable energies in the contemporary distribution of generated energy. A technological supervision is implemented to observe in a systematic manner the behavior of state of the art technologies in renewable energies, in the search of energetic sustainability, making an analysis of the distribution of the most representative Microgrids at world level. it is to be noted, the great inclusion of energy obtained through solar panels, and Eolic generators. However, there is a great participation of generators from diesel vapor, and gas; while in the storage system batteries are predominant, and sometimes, flywheels and supercapacitors surface. These results are possibly due to the promotion and experience of including new techniques and use of energy resource methodologies. Keywords: Renewable Energies, Distributed Generation, Microgrid, Generation Systems, Energetic sustainability. JEL Classifications: Q01, Q4, Q42 DOI: https://doi.org/10.32479/ijeep.9570